Examining Sex Differences in Visual Reliance During Postural Control in Intercollegiate Athletes - Nicolette Ingel; Victoria Vice; Courtney Dommer; Jennifer Csonka; Tara Moore; Ariel Zaleski; Carolyn Killelea; Mallory Faherty; Jody Feld; Timothy Sell (North American Sports Medicine Institute, 2021)
# Background Risk factors for different sports injuries vary between sexes. Deficits in postural stability have been associated with several lower extremity injuries. The purpose of this study was to examine the differences in static postural stability between male and female intercollegiate athletes with and without visual information. # Hypothesis There will be no difference in visual reliance between sexes during static postural stability. # Study Design Cross-sectional Study # Methods Static postural stability was assessed during a single session for football, soccer, basketball, and volleyball intercollegiate athletes (males, n=135, females, n=51) under eyes open (EO) and eyes closed (EC) conditions via performance of single limb stance on a force plate. Ground reaction force component data in all directions were quantified as a unitless composite score (COMP) where lower values indicated better postural stability. The absolute change and percentage change between EO and EC conditions were calculated for each sex. Two-sample Kolmogorov-Smirnov tests were used to compare differences between sexes. # Results Males had greater EO COMP (males=7.77±3.40; females=6.48±4.61; p=0.038; Cohen's d=0.343) and EC COMP (males=19.43±8.91; females 14.66±6.65; p=0.001; Cohen's d=0.571) than females. A significant difference in absolute change from EO to EC was observed between sexes (males=-11.65±7.05; females=-8.18±5.61; p=0.01, Cohen's d=-0.520) indicating that males had a greater change between conditions for the worse. There was no significant difference in percent change from EO to EC between sexes (males=159.2±90.7; females=156.7±109.2; p=0.39; Cohen's d=0.026). # Conclusions The observed differences between males and females in EO COMP, EC COMP, and absolute difference in COMP indicate that there is some factor that causes a difference in static postural stability between sexes. No difference in percent change between groups indicates that the difference in static postural stability between sexes may not be due to visual reliance. Female athletes may inherently have better postural stability than males, but both sexes were able to compensate for the loss of visual input. # Level of Evidence 3